NATIONAL SECURITY EXCUSE FOR THE NE0-PROTECTIONIST TRADE POLICY OF PRESIDENT’S TRUMP ADMINISTRATION - ŁAWNICZAK Ryszard (2018)
In March 2018, the newly elected President of the United States, Donald Trump, surprised the world by triggering a trade war with his largest trading partners. He announced that he would introduce 25% and 10% of customs tariffs on imports of steel and aluminium. Besides he threatened to impose duties on imports of European cars, as well as on the entire list of other products, as long as the trading partners do not stop unfair trading practices and will not reduce their own barriers to American products. In the article, the author tries to explain why protectionist measures of the American administration should be defined as "neo-protectionism", and why and if justly those protectionist steps President Trump justifies as a “threat to national security".